High-current laser-driven beams of relativistic electrons for high energy density research. (12th October 2020) - Rosmej, O N; Gyrdymov, M; Günther, M M; Andreev, N E; Tavana, P; Neumayer, P; Zähter, S; Zahn, N; Popov, V S; Borisenko, N G; Kantsyrev, A; Skobliakov, A; et al.
Abstract: We report on enhanced laser driven electron beam generation in the multi MeV energy range that promises a tremendous increase of the diagnostic potential of high energy sub-PW and PW-class laser systems. In the experiment, an intense sub-picosecond laser pulse of ∼10 19 Wcm −2 intensity propagates through a plasma of near critical electron density (NCD) and drives the direct laser acceleration (DLA) of plasma electrons. Low-density polymer foams were used for the production of hydrodynamically stable long-scale NCD-plasmas. Measurements show that relativistic electrons generated in the DLA-process propagate within a half angle of 1 2 ± 1° to the laser axis. Inside this divergence cone, an effective electron temperature of 10–13 MeV and a maximum of the electron energy of 100 MeV were reached. The high laser energy conversion efficiency into electrons with energies above 2 MeV achieved 23% with a total charge approaching 1 μ C. For application purposes, we used the nuclear activation method to characterize the MeV bremsstrahlung spectrum produced in the interaction of the high-current relativistic electrons with high-Z samples and measured top yields of gamma-driven nuclear reactions. The optimization of the high-Z target geometry predicts an ultra-high MeV photon number of ∼10 12 per shot at moderate relativistic laser intensity of 10 19 Wcm −2 . A good agreement between the experimental data and the results of the 3D-PIC and GEANT4-simulations was demonstrated.